Local Culture-Based Civics Learning Resources for Elementary School: an Ethnopedagogical Study of Topeng Tumenggung Cirebon Performing Arts - Hikmah Aulia Nur Faidah; Malik Fauzi; Ade Subangkit; Iin Wariin Basyari; Auliya Aenul Hayati (Eduvest - Journal of Universal Studies, 2025)
Today's young generation faces great challenges in maintaining cultural identity and building character amid the rapid flow of globalization and technological advancement. Character education through a local culture-based approach is an alternative solution in strengthening the nation's identity. This research focuses on identifying the symbolic meaning and values of local wisdom in the culture of the Tumenggung type Cirebon mask performance art, which can be used as a learning resource for PPKn in elementary schools. The research uses a qualitative approach with interpretive descriptive methods. The research site is the Panji Asmara Art Studio in Bulak Village, Cirebon Regency. Data collection techniques include in-depth interviews, observations, and documentation studies. The main informant is the Cirebon mask artist, a cultural expert. The data analysis technique uses the interactive model of Miles and Huberman, while meaning analysis employs a hermeneutic approach with "thick description" by Geertz. The results of the study show that the performance art of the Tumenggung mask contains values of local wisdom, which include cultural preservation, religious values, character education, and leadership values integrated into elements of movement, accompaniment, costumes, and masks. The conclusion is that the value of local wisdom contained in the performing art of the Tumenggung Cirebon mask can be used as a source of PPKn learning in schools using an ethnopedagogical approach.